Online Learning System for Arabic Teacher Professional Education Program in the Digital Era - Hanifah, Umi; Mukhoiyaroh, Mukhoiyaroh; Gumilar, Rizki (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
One of the serious problems faced by the world of education in this digital era is the low ability of teachers in mastering Information and Communication Technology which has the impact for the quality of learning. This study aimed to enhance the professionalism of Arabic language teachers through the online learning system in Teacher Professional Education program. Qualitative descriptive method was used. The students in the Arabic Teacher Professional Education program at LPTK UIN Sunan Ampel were being the subject of the research. The data was collected through interviews with 5 lecturers, questionnaires distributed to 17 students, observations on the implementation of online learning, and documentation of student assignments. Then it was analyzed critically with data analysis techniques developed by Miles, Huberman, and Saldana. The results showed that the online lectures of Teacher Professional Education students at the LPTK UIN Sunan Ampel which integrated pedagogic and professional materials as in the curriculum structure of Arabic Teacher Professional Education in the online learning system could increase the professionalism of Arabic language teachers which integrated technological, pedagogical and content knowledge can develop teacher competence. The results of this study was intended to increase the quality of online learning in the Teacher Professional Education program and the professionalism of the teachers.